High‐performance polymer‐supported extractants with phosphonate ligands for scandium(III) separation. Issue 7 (27th March 2016) - Cui, Hongmin; Chen, Ji; Li, Hailian; Zou, Dan; Liu, Yu; Deng, Yuefeng
Abstract : As the market demand for scandium has grown, a great deal of interest has been generated in its recovery. To substantially simplify the process and provide a green alternative for scandium separation, novel polymer‐supported extractants containing di(2‐ethylhexyl) phosphonate and bis(2, 4, 4‐trimethylpentyl) phosphonate, [D201][DEHP] and [D201][C272] are proposed because they demonstrate improved adsorption capacity and selectivity toward scandium(III). Scandium(III) adsorption is significantly affected by the solution pH, with the maximum adsorption occurring at a pH of approximately 0.78. The batch adsorption data fit well with the Langmuir isotherm and pseudo‐second‐order kinetic models. A combination of the Fourier transform infrared and XPS spectra suggest that the complexation of oxygen atoms in phosphate groups with scandium(III) is the predominant adsorption mechanism. Additionally, the two resins were used to recover scandium from leaching liquor of nickel laterite ore. [D201][DEHP] exhibits unusual selectivity for scandium and low competitive behavior with other metals, thus increasing its market potential. © 2016 American Institute of Chemical Engineers AIChE J, 62: 2479–2489, 2016